2009
DOI: 10.1159/000229027
|View full text |Cite
|
Sign up to set email alerts
|

Functional Rehabilitation of Mandibular Continuity Defects Using Autologous Bone and Dental Implants – Prognostic Value of Bone Origin, Radiation Therapy and Implant Dimensions

Abstract: Aim: The aim of this retrospective study was to investigate prognostic parameters for the rehabilitation of mandibular continuity defects with free autologous bone and dental implants for patients after intraoral squamous cell carcinoma. Methods: Following potential prognostic factors for implant survival were analyzed: bony bed (local bone versus augmented iliac crest bone), radiation dose (no radiation, <50 Gy, ≥50 Gy) and implant dimensions. Kaplan-Meier survival estimates of the inserted implants were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 98 publications
3
37
0
Order By: Relevance
“…Concerning the radiation dose, the implants inserted into locations irradiated with ≥50 Gray (Gy) in 4 studies had a lower survival rate than implants in locations that are irradiated with <50 Gy. The same happened in another study, but comparing different dose thresholds (>54 vs <54 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the radiation dose, the implants inserted into locations irradiated with ≥50 Gray (Gy) in 4 studies had a lower survival rate than implants in locations that are irradiated with <50 Gy. The same happened in another study, but comparing different dose thresholds (>54 vs <54 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Promising long‐term results for well‐established treatment sites with optimum bone quality, such as the interforaminal region of the lower jaw, 28 have led to a continuous expansion of indications and introduction of more offensive treatment protocols like implantation into augmented areas, immediate implantation following tooth extraction and/or immediate loading of dental implants 29–32 . Furthermore, patients with limitations of tissue homeostasis and integrity like after radiation therapy to the head and neck region or with impaired bone remodeling and repair capacity because of metabolic disorders or systemic medication (e.g., bisphosphonates) have been identified as challenging collectives for the treatment with dental implants 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, irradiation affects angiogenesis (Nemeth et al, 2000;Chiapasco, 1999;Dholam and Gurav, 2012;Klein et al, 2009), several aspects of leukocyte development and function, as well as host cytokine levels (Nemeth et al, 2000;Granstrom, 2003;Dholam and Gurav, 2012;Klein et al, 2009), which could partially explain the lower success rates observed in the aforementioned studies.…”
Section: Comparison With Other Studies or Reviewsmentioning
confidence: 99%